Characterization of clays from the red ceramic industry in the City of Crato – Ceará, Brazil (Research, Society and Development, 2021)
Among the numerous ceramic products, red ceramic products, also known in Brazil as structural ceramics, used in civil construction stand out. The raw material for the production of red ceramics is clay, a low-cost mineral that comes from the disintegration of rocks. The red ceramic industry is a very important economic activity due to the generation of jobs and income for the Cariri region. Thus, in order to obtain a better understanding of the properties of the clay materials used and to determine ideal conditions for the manufacture of different types of ceramic pieces with them, this research aimed to characterize three clays collected in a ceramic industry located in the municipality of Crato-CE. The samples were previously processed by crushing, grinding, sieving and kiln dried at 110 ° C. Then, its characteristics were evaluated by the following techniques: X-ray fluorescence (FRX), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The results indicated high levels of SiO2, Al2O3 and Fe2O3 for all clays, as well as high percentages of K2O melting oxide for clays A2 and A3; different Al2-OH, Si-O, Si-O-Al and Si-OH vibrations characteristic of the functional groups belonging to the clay mineral structures; grains of lamellar and rounded shapes, agglomerated and dispersed; and concentrations close to 100%, of fractions less than 2 µm for all samples. In general, clays showed potential for the production of tiles, bricks and ceramic blocks provided there is strict control of granulometry.